sp 3 C–H oxidation by remote H-radical shift with oxygen- and nitrogen-radicals : a recent update - Chiba, Shunsuke (2014)
This review updates on recent advances in aliphatic sp3 C–H bond oxidation by remote H-radical abstraction with oxygen- and nitrogen-radicals classifying by the type of the radical precursors.